Class Discussion, Projects, and Critical Thinking Exercises: Thinking Critically About the Size of Today’s Immigration - Chapkina, Nadejda; Jaret, Charles; Liu, Guangya; Pollock, Angela (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
"The numbers don’t lie." "The numbers speak for themselves." "You can find a statistic to prove just about anything you want to prove." These, or similar comments, are heard in debates about immigration and other controversial topics. We contend that numbers or statistics "don’t speak for themselves" and must be interpreted. Moreover, different interpretations or "spins" on the same numbers are likely if people look at them from different perspectives. Students should learn how to look at immigration data from several perspectives and to know when data are being used to bolster one point of view and neglect another.